Lived Experiences Among Grade 10 Students in Playing 4 Pics 1 Word for Vocabulary Learning - Cristie Ann L. Jaca; Bernardo M. Tumulak III; Verner V. Boaquin (RIRAI Publisher, 2023)
This qualitative study unraveled the lived experiences among Grade-10 (Wisdom) Students of Tuyan National High School in playing the mobile word game 4 Pics 1 Word. The data were gathered through one-on-one interviews using researcher-made questionnaires and analyzed using the Braun and Clarke (2006) six-phase framework for doing thematic analysis, particularly semantic and latent approaches. Based on the findings of the study, the themes that emerged from the students' responses were: challenged, engaged, enhanced critical thinking skills, and increased vocabulary skills which show that students have varied learning experiences. Moreover, the study found that the students’ experiences in playing the word game helped them develop an interest in learning new words, increase their self-confidence in expressing themselves, improved analyzation skills, and improved reading comprehension skills. This implies that their gamified learning experience helped them improve their vocabulary skills and attitudes toward learning vocabulary. Further, this study concludes that gamified learning, surrogated with image presentations, is lucrative to students' experiences in learning vocabulary thus gamified teaching of vocabulary should be imposed.